2022
DOI: 10.1001/jamanetworkopen.2021.42282
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity, Diabetes, and Alcohol Use With Liver Fibrosis Among US Adults With Hepatitis C Virus Infection

Abstract: HIV infection, obesity, and diabetes are associated with advanced stages of fibrosis in HCV. [1][2][3][4][5] However, these risk factors are likely interdependent and potentially exacerbated by other conditions that may contribute to liver fibrosis. 6 Identifying patients with HCV who are at risk for advanced fibrosis is important for evidence-based, efficient HCC screening practices. We therefore examined the association of HCV, obesity, diabetes, and alcohol use with liver fibrosis by using electronic health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Simultaneously, we observed that differential gene expression also affects the regulation of viral transcription. Migdal et al 42 similarly found that obesity can accelerate the progression of liver fibrosis in patients with hepatitis C virus infection. Previous studies have also confirmed that the risk of HCC significantly escalates when hepatitis C virus infection patients concurrently experience alcoholism or obesity, with the odds ratio increasing from 8–12 to 48–54 43 45 .…”
Section: Discussionmentioning
confidence: 97%
“…Simultaneously, we observed that differential gene expression also affects the regulation of viral transcription. Migdal et al 42 similarly found that obesity can accelerate the progression of liver fibrosis in patients with hepatitis C virus infection. Previous studies have also confirmed that the risk of HCC significantly escalates when hepatitis C virus infection patients concurrently experience alcoholism or obesity, with the odds ratio increasing from 8–12 to 48–54 43 45 .…”
Section: Discussionmentioning
confidence: 97%
“…It is estimated that progression to cirrhosis is 16% at 20 years and 41% at 30 years [6,7]. In addition, HCV complications (i.e., ascites, encephalopathy), diabetes mellitus, obesity, and high active alcohol use are associated with advanced fibrotic stages [8]. The most relevant complication is hepatocellular carcinoma, whose annual incidence is close to 3% [9].…”
Section: Introductionmentioning
confidence: 99%